TIPE DAN GAYA KEPEMIMPINAN PENDIDIKAN DAN DAKWAH - Nadzmi Akbar (UIN Antasari Banjarmasin, 2017)
Leadership style adopted by a leader in educational institutions, will mentukan atmosphere and climate in the next educational institutions also determine the effectiveness of health efforts in the purpose of education. Leadership is born with a process, not innate from birth to be able and trained to achieve the competence of leadership that berkulaitas, so that in the institutional education can achieve optimal effectiveness. The style of leadership is the way used in the leadership process that is implemented in a person's task to face each other for what he wants. There are two styles of leadership that is style of leadership style, leadership style, leadership style. Dakwaha leadership style is a leader who is able to bring society to success in the pleasure of Allah SWT. In this case the leader will always appear to achieve the benefit and welfare of his followers for the salvation of the life of the world and the hereafter. Thus the style seoarang da'wah leaders and education will not be separated from three things as a mentor, as a model and as a practitioner. Dakwah leadership style is a model and style of leadership with its own formulation.